Yb(OTf)3-Catalyzed Bromination Reactions of Natural Product-like N-Benzyl Cinnamamides: A Facile Route to Diverse N-Substituted Amides of Pharmacological Interest (2013)
Diverse natural product-like N-benzyl cinnamamides were prepared by condensation of trans-cinnamic acid with substituted benzylamines in the presence of boric acid as catalyst. The further evaluation of this amides as a substrates of the bromo-arylation reaction, in the presence of N-bromosuccinimide (NBS) as the halogen source and under the catalysis of Yb(OTf)3, generate a different types of N-substituted amides: N-aryl 2,3-dibromopropanamides, N-(2-bromobenzyl) cinnamamides and tetrahydro-2-benzazepin-3-one as a new molecules. Here we discuss the formation of these main products on the basis of the electronic nature of the substituents present in the N-benzyl aromatic ring of the prepared cinnamamides.